Economic Integration and Location of Manufacturing Activities: Evidence from Mercosur - Pablo Sanguinetti; Iulia Traistaru; Christian Volpe Martincus (European Regional Science Association (ERSA), 2004)
Economic integration leads to a reallocation of resources across sectors and space. Location patterns resulting from North-North and North-South regional trade initiatives have been documented in several studies. However, empirical evidence on South-South agreements is rather limited. In this respect, MERCOSUR provides an interesting case study. This paper aims at answering the following questions: What are the main driving factors explaining location patterns in the Southern Cone? To what extent has the establishment of MERCOSUR affected location of economic activities? Using data for the period 1985-1998, we identify the determinants of manufacturing location patterns and assess their changes in the context of increased economic integration. We find that preferential trade liberalization has fostered the influence of factors underlined by the recent trade theories, such as economies of scale and input-output linkages, relative to comparative advantage considerations. Keywords: Economic Integration, Location of Industrial Activities, MERCOSUR JEL-Classification: F14, F15, L60
Keywords: F14; F15; L60; 330; Economic Integration; Location of Industrial Activities; MERCOSUR